2000
DOI: 10.1039/b000730g
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on proton transfer in the mutarotation of sugars

Abstract: The epimerisation process of the model sugar 2-tetrahydropyranol was studied by means of ab initio calculations. The results suggest that the rate limiting step of sugar ring opening involves a high-energy intramolecular proton transfer reaction or a low-energy process in which the proton transfer is mediated by a catalyst molecule, formic acid in the case investigated. The catalysed process is an asynchronous concerted double proton transfer reaction, where both protons are transferred within the same element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
7
30
0
Order By: Relevance
“…A systematic study shows that if X has a proton affinity between that of O and C of CO the barrier for rearrangement completely disappears (Chalk & Radom, 1997). Other examples of rearrangements of protonated or cationized species involving assisted proton (or even alkyl cation) transport have been reported so far, from small species HNNO + /NNOH + (Ferguson, 1989), CH 3 CO + /CH 3 OC + (Cunje et al, 1998) to 2‐tetrahydropyranol, a model for the study of sugar epimerization (Morpurgo et al, 2000).…”
Section: Structural and Energetic Aspects Of The Protonationmentioning
confidence: 97%
“…A systematic study shows that if X has a proton affinity between that of O and C of CO the barrier for rearrangement completely disappears (Chalk & Radom, 1997). Other examples of rearrangements of protonated or cationized species involving assisted proton (or even alkyl cation) transport have been reported so far, from small species HNNO + /NNOH + (Ferguson, 1989), CH 3 CO + /CH 3 OC + (Cunje et al, 1998) to 2‐tetrahydropyranol, a model for the study of sugar epimerization (Morpurgo et al, 2000).…”
Section: Structural and Energetic Aspects Of The Protonationmentioning
confidence: 97%
“…66 The mutarotation process has also been the subject of theoretical research using quantum mechanical methods. 67,68 Theoretical calculations have shown that mutarotation is assisted by solvents and that the rst molecule acts as a catalyst, playing a crucial role in the reaction. 69 Monosaccharides can be obtained from various waste products of the sugar, agricultural and food industries.…”
Section: Sucrose and Waste Biomass From Processing Of Sugar Beets As mentioning
confidence: 99%
“…[4] Numerous related investigations have been reported on the cyclic and open-chain tautomers' equilibria of simple sugars, mostly involving hexoses. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Spectroscopic studies of mutarotation of monosaccharides in the aqueous solution, [8][9][10] pure anhydrous [25][26][27][28][29][30][31] and crystalline [32,33] states have been an active research field. In the gas phase, an initial step of the anomerization reaction is thought to entail both migrating of the hydrogen atom from the hydroxyl group linked to the anomeric carbon (C1) to the ring oxygen and bond breaking between the ring oxygen and the anomeric carbon to form an open-chain intermediate (for the aldose case, this step is illustrated in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Interconversion of this type called mutarotation or anomerization, was first observed for d ‐glucose in the aqueous solution . Numerous related investigations have been reported on the cyclic and open‐chain tautomers' equilibria of simple sugars, mostly involving hexoses …”
Section: Introductionmentioning
confidence: 99%